FEATURES OF PERSONALITY AND PROFESSIONAL ABILITIES OF A TEACHER OF A PRESCHOOL EDUCATIONAL ORGANIZATION - Shokhista Rabidjanovna Samarova (European Science Publishing, 2024)
The article describes the tasks of education according to scientists. The personality of the educator plays an important role in education. Education is effective when the teacher is attentive to the educational process.
Keywords: education, personality of a teacher, concepts of preschool education.